Vitamin D supplementation and prevention of cardiovascular disease and cancer in the Finnish Vitamin D Trial-a randomized controlled trial - Virtanen Jyrki K; Nurmi Tanja; Aro Antti; Bertone-Johnson Elizabeth R; Hyppönen Elina; Kröger Heikki; Lamberg-Allardt Christel; Manson JoAnn E; Mursu Jaakko; Mäntyselkä Pekka; Suominen Sakari; Uusitupa Matti; et al. (Elsevier, 2025)
Background: Vitamin D insufficiency is associated with risk of cardiovascular diseases (CVD) and cancer in observational studies, but evidence for benefits with vitamin D supplementation is limited.
Objectives: To investigate the effects of vitamin D3 supplementation on CVD and cancer incidence.
Design: The study was a 5-year randomized placebo-controlled trial among 2495 male participants ≥ 60 years and post-menopausal female participants ≥ 65 years from a general Finnish population who were free of prior CVD or cancer. The study had three arms: placebo, 1600 IU/day or 3200 IU/day vitamin D3. Follow-up was by annual study questionnaires and national registry data. A representative sub-cohort of 551 participants had more detailed in-person investigations. The primary endpoints were incident major CVD and invasive cancer. Secondary endpoints included the individual components of the primary CVD endpoint (myocardial infarction, stroke, and CVD mortality), site-specific cancers and cancer death.
Results: During the follow-up, there were 41 (4.9%), 42 (5.0%) and 36 (4.3%) major CVD events in the placebo, 1600 IU/d (vs. placebo: hazard ratio (HR), 0.97;95% CI, 0.63,1.49; P = 0.89), and 3200 IU/d (HR, 0.84;95% CI, 0.54,1.31; P = 0.44) arms, respectively. Invasive cancer was diagnosed in 41 (4.9%), 48 (5.8%) and 40 (4.8%) participants in the placebo, 1600 IU/d (HR, 1.14;95% CI, 0.75,1.72; P = 0.55), and 3200 IU/d (HR, 0.95;95% CI, 0.61,1.47; P = 0.81) arms, respectively. There were no significant differences in the secondary endpoints or total mortality. In the sub-cohort, the mean (standard deviation) baseline serum 25-hydroxyvitamin D concentration was 75 (18) nmol/L. After 12 months, the concentrations were 73 (18) nmol/L, 100 (21) nmol/L and 120 (22) nmol/L in the placebo, 1600 IU/d and 3200 IU/d arms, respectively.
Conclusions: Vitamin D3 supplementation did not lower the incidence of major CVD events or invasive cancer among older adults, possibly due to sufficient vitamin D status in most participants at baseline. Clinical Trial Registry number: ClinicalTrials.gov: NCT01463813, https://clinicaltrials.gov/ct2/show/NCT01463813.